The Impact of Plasma Protein Binding Characteristics and Unbound Concentration of Voriconazole on Its Adverse Drug Reactions - Yuan, Zi-Qing-Yun; Qiao, Chun; Yang, Zhi-Cheng; Yu, Lei; Sun, Lu-Ning; Qian, Yi; Zhang, Xue-Hui; Meng, Ling; Zhang, Xiao-Yan; Wang, Yong-Qing (Frontiers in Pharmacology, 2020)
This study investigated voriconazole (VRC) unbound plasma concentration and it’s relationship with adverse drug reactions (ADRs) in patients with malignancy hematologic disease. Plasma samples were collected from patients or spiked in vitro. A time-saving rapid equilibrium dialysis assay is used for the separation of unbound and bound VRC, following a high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) analysis method for drug concentration detection. Liver function and treatment details were collected from the patient’s electronic medical records. Protein concentration was determined according to instructions. VRC plasma protein binding rate (PPB) in patients is significantly higher [69.5±6.2%] than that in vitro samples, influenced by total drug concentration (Ct), plasma protein concentration and protein type. The α1-acid glycogen (AAG) has the highest affinity with VRC. Relationship between total PPB of VRC with PPB of individual protein is not a simple addition, but a compressive combination. Unbound drug concentration (Cu) of VRC shows significant relationships with Ct , protein concentration, AST level, metabolism type of CYP2C19 and co-administration of high PPB medicines. Unbound plasma concentration of VRC shows a more sensitive relationship with ADRs than Ct.